Harmful use of alcohol: - Ferreira-Borges, Carina (2018)
Alcohol consumption and alcohol-attributable burden of disease in Africa are expected to rise in the near future, yet. increasing alcohol-related harm receives little attention from policymakers and from the population in general. Even where new legislation is proposed it is rarely enacted into law. Being at the center of social and cultural activities in many countries, alcohol’s negative role in society and contribution to countries’ burden of disease are rarely questioned. After the momentum created by the adoption in 2010 of the WHO Global Strategy and the WHO Regional Strategy (for Africa) to Reduce the Harmful Use of Alcohol, and the WHO Global Action Plan for the Prevention and Control of Non-Communicable Diseases, in 2013, little seems to have been done to address the increasing use of alcohol, its associated burden and the new challenges that derive from the growing influence of the alcohol industry in Africa. In this review, we argue that to have a positive impact on the health of African populations, action addressing specific features of alcohol policy in the continent is needed, namely focusing on particularities linked to alcohol availability, like unrecorded and illicit production, outlet licensing, the expansion of formal production, marketing initiatives and taxation policies.